Do the Poor Count? : Democratic Institutions and Accountability in a Context of Poverty - Taylor-Robinson, Michelle M. (Book collections on Project MUSE., 2010)
"With specific focus on Brazil and Honduras, examines electoral and nominating institutions and clientelism in Latin America, and the capacity of poor people to monitor and sanction officials"--Provided by publisher